2004
DOI: 10.1111/j.1525-1446.2004.21103.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Homelessness in Women

Abstract: The specific aims of the article were to: (i) compare childhood experiences of intimacy and autonomy as they occurred in the families of origin of women who have and women who have not experienced homelessness; (ii) compare social support, reciprocity, and conflict as they occurred in the childhood support networks and in the current support networks of women who have and women who have not experienced homelessness; (iii) examine the relationships between intimacy and autonomy in families of origin and the soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 55 publications
3
27
1
Order By: Relevance
“…Further, the homeless women reported more conflict in their relationships than the housed women. This finding is echoed in an Anderson and Rayens (2004) study of 255 women, of whom 98 were homeless, 88 had never been homeless but experienced childhood trauma (physical and/or sexual abuse), and 73 had never been homeless and did not experience childhood trauma. When compared to the two groups of non-homeless women, the homeless women had significantly lower levels of social support and significantly higher levels of relationship conflict.…”
Section: Social Supportmentioning
confidence: 46%
“…Further, the homeless women reported more conflict in their relationships than the housed women. This finding is echoed in an Anderson and Rayens (2004) study of 255 women, of whom 98 were homeless, 88 had never been homeless but experienced childhood trauma (physical and/or sexual abuse), and 73 had never been homeless and did not experience childhood trauma. When compared to the two groups of non-homeless women, the homeless women had significantly lower levels of social support and significantly higher levels of relationship conflict.…”
Section: Social Supportmentioning
confidence: 46%
“…In addition, homelessness has adverse effects on parenting behavior (Torquati, 2002). Due to the range of stressors linked to homelessness, homeless mothers are less able to support and offer reciprocity to young children (Anderson & Rayens, 2004). Given the important links between a mother's mental health and a child's well‐being, consultants must bring attention to the parent and the child.…”
Section: Children and Parents In Homeless And Domestic Violence Sheltersmentioning
confidence: 99%
“…The parent's availability and ability for relationships may be understandably compromised, yet are crucial for mitigating the effects of extreme forms of stress (e.g., homelessness and domestic violence) on the child's personality development (Bradley, 2007). Recent studies (Anderson & Rayens, 2004; Harpaz‐Rotem, Rosenheck, & Desai, 2009) of homeless mothers have demonstrated an association between a mother's mental status and her child's well‐being, and have suggested that treatment of the mother's symptoms influences the child's mental health.…”
Section: Children and Parents In Homeless And Domestic Violence Sheltersmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of macro (poverty, low-wage jobs, welfare reform, lack of affordable housing, lack of health insurance) and micro (domestic violence, mental illness, substance abuse) level factors are related to homelessness (Anderson & Rayens, 2004). For instance, unemployment, money problems, and drug and alcohol abuse were the most prevalent reasons for homelessness among 230 homeless individuals (O'Toole et al, 2007).…”
Section: Introductionmentioning
confidence: 99%